Efficacy of pre-emergence and post-emergence herbicides for weed management in groundnut (Arachis hypogaea L.) production in Guinea Savannah (International Journal of Scientific Research and Management (IJSRM), 2020)
Groundnut or peanut (Arachis hypogaea L.) has gained prominence as food and cash crop both in the domestic and export markets. In Ghana, the bulk of groundnut is produced in the Guinea savannah zone where it is vulnerable to weed infestation that results in average yields of about 800 kg/ha compared to developed countries of more than 3,000 kg/ha. This experiment was conducted in Tolon during the 2012 farming season to determine the most suitable combination of pre-emergence and post-emergence herbicides and/or hand weeding that could enhance efficient weed control and to assess the treatments that could promote yield and yield components of groundnut. Some local available herbicides and recommended rates used included: Pendimethalin at 0.15 kg a.i./ha, gallant super at 0.03 kg a.i./ha, agil at 0.02 kg a.i./ha, basagran at 0.14 kg a.i./ha. The study was laid out in RCBD with four replications. Results showed Pendimethalin at 0.15 kg a.i./ha plus gallant super at 0.03 kg a.i/ha at 4 weeks after planting (WAP) recorded the highest pod yield of 2436 kg/ha. All treatments recorded significantly high yield over the Weedy check. Weed biomass correlated negatively (r= -0.5074) with nodulation count while haulm yield showed a positive correlation coefficient of (r=0.4575*) with pod yield. Weed control efficiency of 94.8% showed pendimethalin at 0.15 kg a.i/ha plus agil at 0.02 kg a.i/ha at 4WAP was most effective in weed control. Herbicide application reduced weed index. Basagran at 0.14 kg a.i/ha at 4WAP plus one hand weeding at 7WAP recorded least weed index of 24%. The most dominant weeds were broadleaves such as Ageratum conyzoides (L), Corchorus olitorius (Linn) and Ludwigia abyssinica (A. Rich). Plots with uncontrolled weeds resulted in 69% loss of pod yield. In order of decreasing weed control, yield components and pod yield; Pendimethalin at 0.15 kg a.i./ha plus gallant super at 0.03 kg a.i/ha applied at 4 WAP was more effective than basagran at 0.14 kg a.i/ha at 4WAP plus 1HW at 7WAP and gallant super at 0.03 kg a.i/ha at 4 WAP plus 1HW at 7 WAP; and are recommended in that order to groundnut farmers in the Guinea savanna zone of Ghana.